Quantitative Analysis of Post-Bureaucratic Organizational Culture Dynamics in the Regional Secretariat of Brebes Regency - Arifin, Muhammad Ilham Amrul (Spirit Publik: Jurnal Administrasi Publik, 2026)
This study aims to analyze the implementation of organizational culture from a post-bureaucratic governance perspective at the Brebes Regency Regional Secretariat. This study was motivated by demands for bureaucratic reform that lead to more adaptive, collaborative, and results-oriented governance. The study employed a descriptive quantitative approach, involving 52 State Civil Apparatus (ASN) within the Regional Secretariat as respondents. Data collection was conducted through a structured questionnaire based on the main dimensions of post-bureaucratic culture: flexibility, collaboration, participation, and innovation orientation. The data obtained were then analyzed descriptively using SPSS to generate a mean value, standard deviation, and minimum and maximum scores. The analysis results showed a mean value of 78.25 with a standard deviation of 7.438 and a score range of 63 to 90. Based on the classification using the theoretical interval approach, employee perceptions of the implementation of post-bureaucratic culture tended to be positive. Most respondents demonstrated work behavior patterns aligned with post-bureaucratic principles, particularly in the aspects of collaboration and openness to innovation. In general, the organizational culture at the Brebes Regency Secretariat reflects the adoption of post-bureaucratic values. However, its implementation remains hybrid. On the one hand, the organization retains Weberian characteristics such as formal hierarchy and regulatory compliance. On the other hand, daily work practices are beginning to demonstrate increased collaboration, the use of digitalization, and a drive for innovation. Therefore, strengthening organizational culture through transformational leadership and systematic performance measurement are crucial steps to ensure that cultural transformation truly impacts the quality of public services.